Pengaruh Internship Development Terhadap Career Readiness Peserta Magang Di Hotel Four Points By Sheraton Batam - Alia Putri; Feriantano Sundang Pranata; Yunus Supriharto (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
The primary objective of this study is to examine the impact of internship development on the career readiness of interns at the Four Points by Sheraton Batam Hotel. A quantitative methodology utilizing a causal associative research design was adopted. The target population comprised 60 participants who concluded their internship program at the establishment between January 2025 and January 2026. Employing a saturated sampling technique, the entire population was utilized as the study cohort. Data acquisition was conducted via a Likert-scale questionnaire. Subsequent data analysis involved tests for normality, homogeneity, and linearity, alongside simple linear regression, coefficient of determination evaluation, and partial t-tests, all executed using SPSS version 27.0. The findings demonstrate that internship development exerts a positive and statistically significant influence on the career readiness of the participants. This conclusion is supported by a calculated t-value of 15.023, which exceeds the t-table value of 2.002 (15.023 > 2.002), alongside a significance level of 0.000 < 0.05. Additionally, the coefficient of determination (R Square) of 0.796 reveals that internship development accounts for 79.6% of the variance in career readiness, with the remaining 20.4% attributable to extraneous variables not examined within this research”. Consequently, the study concludes that enhanced implementation of internship development directly correlates with elevated levels of career readiness among interns.